Insurance Product Design and its Effects: Trade-offs along the Managed Care Continuum - Peter Kemper; Ha T. Tu; James D. Reschovsky; Elizabeth Schaefer (SAGE Publishing, 2002)
This paper uses 1996-97 Community Tracking Study data to analyze the effects of different insurance product designs on service use, access, and consumer assessments of care for nonelderly people with employer-sponsored insurance. Product types are defined by features including use of networks, gatekeeping, capitation, and group/staff model delivery systems. We found no evidence of differences across product types in unmet need or delayed care or use of hospitals, surgery, or emergency rooms. At the same time, different product designs present purchasers with a clear trade-off between paying more out of pocket and encountering more administrative barriers to care. In addition, an increasing proportion of consumers report dissatisfaction with choice of physicians and low trust in physicians as one moves along the managed care continuum from unmanaged to heavily managed products. Our findings have implications for efforts to regulate managed care. The existence of a trade-off between out-of-pocket costs and administrative barriers to care means that some forms of regulation run the risk of reducing choices available to consumers. This is particularly true of regulations that would change the nature of managed care products by prohibiting the use of specific care management tools. To the extent that the backlash against managed care targets restrictions on choice and administrative hassles among consumers who nonetheless choose more heavily managed products because of their lower cost, eliminating heavily managed products would leave those consumers worse off.